The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1371/journal.pone.0194389
|View full text |Cite
|
Sign up to set email alerts
|

Foraging areas, offshore habitat use, and colony overlap by incubating Leach’s storm-petrels Oceanodroma leucorhoa in the Northwest Atlantic

Abstract: Despite their importance in marine food webs, much has yet to be learned about the spatial ecology of small seabirds. This includes the Leach’s storm-petrel Oceanodroma leucorhoa, a species that is declining throughout its Northwest Atlantic breeding range. In 2013 and 2014, we used global location sensors to track foraging movements of incubating storm-petrels from 7 eastern Canadian breeding colonies. We determined and compared the foraging trip and at-sea habitat characteristics, analysed spatial overlap am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 45 publications
2
53
0
Order By: Relevance
“…In comparison, Hedd et al. () reported that Leach's Storm‐Petrels in the Atlantic Ocean ranged up to 830 km from breeding colonies during incubation. Other small Procellariiform seabirds are also known to forage over large areas when breeding (Pollet et al.…”
Section: Discussionmentioning
confidence: 97%
“…In comparison, Hedd et al. () reported that Leach's Storm‐Petrels in the Atlantic Ocean ranged up to 830 km from breeding colonies during incubation. Other small Procellariiform seabirds are also known to forage over large areas when breeding (Pollet et al.…”
Section: Discussionmentioning
confidence: 97%
“…Another potential cause for declining population trends is strandings associated with light pollution from the offshore oil and gas industry (Wiese et al 2001, Montevecchi 2006, Ronconi et al 2015. However, foraging ranges of storm-petrels nesting at colonies located in northern Nova Scotia and the east coast of Newfoundland overlap with offshore oil and gas platforms, yet the foraging range of Kent Island storm-petrels does not (Hedd et al 2018), suggesting that this source of potential mortality is not a factor for the Kent island colony. Chronic oil spills within seabird foraging ranges also pose risk of increased mortality (Wiese and Robertson 2004).…”
Section: Breeding Population Status and Trendmentioning
confidence: 99%
“…Some breeding species such as Brown Skua Catharacta antarctica, Broad-billed Prion Pachyptila vittata or MacGillivray's Prion Pachyptila macgillivrayi were not included in our hotspot assessment because these species have only been tracked with Global Location Sensing (GLS) loggers, which have too large uncertainty for our analysis (Dias et al, 2017;Phillips et al, 2004). Other small seabird species, notably storm-petrels, diving petrels and terns, have not been tracked so far, and while terns likely remain within the EEZ during the breeding season, storm-petrels are very mobile and may utilize areas far away from their breeding grounds (Hedd et al, 2018;Oppel et al, 2018). The absence of data for smaller species may result in an overemphasis of existing data, such as the hotspots identified from Sooty Albatross tracking data in autumn, which may be due to the preference of a small number of individuals and treated with caution.…”
Section: Discussionmentioning
confidence: 99%